2012
DOI: 10.3892/ijmm.2012.1061
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Typhae total flavone improves insulin-induced glucose uptake through the β-arrestin-2-mediated signaling in C2C12 myotubes

Abstract: Defects in insulin-stimulated glucose uptake in skeletal muscle result from the dysfunction of insulin signaling including the phosphatidylinositol-3 kinase (PI3K) pathway and a novel β-arrestin-2-mediated signaling, which leads to insulin resistance (IR). Pollen Typhae, a Chinese herb, has been used for thousands of years in traditional Chinese medicine, and has the potential to inhibit the development of IR. We have previously reported that Pollen T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…We have reported that free fatty acid (palmitate) contributes to insulin resistance 15) and that PTF prevents palmitate-induced impairment of glucose uptake in C2C12 myotubes. 6) Interestingly, rosiglitazone also obviously reduced TG and LDL-c levels, which was in accordance with PTF and the past reports. 7,16) At present, although thiazolidinediones, the agonists of peroxisome proliferator-activated receptors-γ such as rosiglitazone and pioglitazone, have been widely used to treat type 2 diabetes, some deleterious side effects including weight gain, and increasing risk of CVD in type 2 diabetes patients also coexist.…”
Section: )supporting
confidence: 91%
See 2 more Smart Citations
“…We have reported that free fatty acid (palmitate) contributes to insulin resistance 15) and that PTF prevents palmitate-induced impairment of glucose uptake in C2C12 myotubes. 6) Interestingly, rosiglitazone also obviously reduced TG and LDL-c levels, which was in accordance with PTF and the past reports. 7,16) At present, although thiazolidinediones, the agonists of peroxisome proliferator-activated receptors-γ such as rosiglitazone and pioglitazone, have been widely used to treat type 2 diabetes, some deleterious side effects including weight gain, and increasing risk of CVD in type 2 diabetes patients also coexist.…”
Section: )supporting
confidence: 91%
“…19) Because of the improvement of insulin sensitivity and few side effects, it is likely that PTF is a potential choice for the treatment of type 2 diabetes. We have reported that PTF improves insulin resistance involving the β-arrestin-2-mediated signaling in C2C12 myotubes, 6) which is different from rosiglitazone that mainly activates peroxisome proliferator-activated receptors-γ referring to the phosphatidylinositol-3 kinase (PI3K) insulin signal pathway. 20) Fig.…”
Section: )mentioning
confidence: 95%
See 1 more Smart Citation
“…The protein expression of VEGF and bFGF in granulation tissue from eight-day-old wounds was determined by western blotting, as previously described with certain modifications (37). Briefly, tissue homogenates from wound granulation were prepared using RIPA lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Pollen Typhae has been widely used to treat type 2 diabetes and other diseases characterized by insulin resistance such as metabolic syndrome and non-alcohol fatty liver disease in China. We have ever reported that Pollen Typhae total flavone (PTF), the extract from Pollen Typhae which mainly contains typhaneoside and other constituents (Feng et al 2012a), ameliorates insulin resistance in type 2 diabetic rats (Feng et al 2014), but the potential mechanisms remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%